(x + y)^2 + (x - y)^2 is equals to
2xy
3xy
4xy
none of these
Answers
Answered by
0
Step-by-step explanation:
= none of these
(x+y)2 = x2 + y2 +2xy
(x-y)2 = x2 + y2 -2xy
By adding it, we get :
2x2 + 2y2
= 2(x2 + y2)
Hope this helps you. Stay safe.
Attachments:
![](https://hi-static.z-dn.net/files/dac/eb4a9e4969d43ca7b5f138ac152ab606.jpg)
Answered by
0
Answer:
d is the correct answer (solved in the uploaded photo)
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/df7/134f204d24e2b7a35bac0b167b27ab6c.jpg)
Similar questions